2014
DOI: 10.1159/000370256
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of a Female Fetus with Ring Chromosome 9, 46,XX,r(9)(p24q34), and a de novo Interstitial 9p Deletion

Abstract: Ring chromosomes are circular structures formed as a result of breaks in the chromosome arms and the fusion of the proximal broken ends with a loss of distal material, or by fusion of dysfunctional telomeres without any loss. The mechanism underlying this process has not yet been sufficiently explained. Commonly, rings occur as acquired genetic abnormalities; however, sometimes they are found as constitutional aberrations with a prevalence of around 1:50,000 live births. Here, we present a new case of r(9) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The infectious complications, which candidate genes could be CD274 and IL33 at 9p24.1, were seen in the r(9) patient of Qin et al (2016). The four patients with deletion of 9q involving the EHMT1 gene showed features of 9q34.3 deletion syndrome (La Cour Sibbesen et al, 2013; Penacho et al, 2014; Lyu et al, 2019, and present patient). Other phenotypic variations could be caused by triple‐sensitivity genes from an extra duplication in the r(9) of Marsudi et al (2018) and the present patient.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The infectious complications, which candidate genes could be CD274 and IL33 at 9p24.1, were seen in the r(9) patient of Qin et al (2016). The four patients with deletion of 9q involving the EHMT1 gene showed features of 9q34.3 deletion syndrome (La Cour Sibbesen et al, 2013; Penacho et al, 2014; Lyu et al, 2019, and present patient). Other phenotypic variations could be caused by triple‐sensitivity genes from an extra duplication in the r(9) of Marsudi et al (2018) and the present patient.…”
Section: Discussionmentioning
confidence: 62%
“…Review of literature found seven patients of r(9) with clinical and cytogenomic findings, including one prenatal fetus (Penacho et al, 2014) and six postnatal patients (La Cour Sibbesen, Jespersgaard, Alosi, Bisgaard, & Tümer, 2013; Laursen et al, 2015; Sivasankaran, Kanakavalli, Anuradha, Samuel, & Kandukuri, 2016; Qin et al, 2016; Marsudi et al, 2018; Lyu, Li, Li, Shang, & Ma, 2019). Ring chromosome instability index (RCII) was defined as the percentage of cells with ring chromosome variants and loss of ring chromosome.…”
Section: Methodsmentioning
confidence: 99%